Antineoplastic drug NSC631570 modulates functions of hypoxic macrophages - Skivka, L.M.; Fedorchuk, O.G.; Rudic, M.P.; Pozur, V.V.; Khranovska, N.M.; Grom, M.Yu.; Nowicky, J.W. (Цитология и генетика, 2013)
Hypoxia is an important factor in the macrophages microenvironment. Many physiological and pathological processes including solid tumor development are characterized by both low oxygen content and presence of macrophages. Tumor-associated hypoxia causes alternative polarization of macrophages in tumor tissue and transformation of these cells into the allies of a malignant neoplasm. The aim of the work was to investigate the effect of NSC631570, a cancerselective drug that is known to selectively accumulate in the tumor tissue, on hypoxic macrophage function. Murine peritoneal macrophages (PMs) were subjected to hypoxia (3% O₂). Nitrite level was assayed by the Griess reaction. Arginase activity was measured by colorimetric method. ROS generation and phagocytosis was estimated by flow cytometry. O₂⁻ generation was assayed by the NBT reduction method. HMGB1 expression was determined by ELISA. 42 h hypoxia caused alternative polarization of murine PMs with significant arginase prevalence. NSC631570 repolarized arginine metabolism of hypoxic macrophages to NOS dominant and activated their pro-inflammatory functions: recovered ROS production and increased alarmin releaseNSC631570 can restore pro-inflammatory functions of macrophages, alternatively polarized by hypoxia. Гипоксия является важным фактором микроокружения макрофагов. Многие физиологические и патологические процессы, в том числе рост солидных опухолей, характеризуются низким давлением кислорода и присутствием макрофагов. Опухолеассоциированная гипоксия является одной из причин альтернативной поляризации макрофагов в опухолевой ткани, превращая их в клетки-союзники опухолевого процесса. Целью работы было исследование влияния NSC631570 – опухоле-селективного препарата со способностью избирательно накапливаться в опухолевой ткани – на функции гипоксических макрофагов. Мышиные перитонеальные макрофаги (ПМ) подвергались гипоксической обработке (3 % O₂). Уровень нитритов исследовали в реакции Грисса. Аргиназную актив-ность определяли колориметрическим методом. Образование внутриклеточных реактивных форм кислорода (РФК) и фагоцитоз анализировали c помощью проточной цитофлюориметрии. Внеклеточную продукцию РФК определяли в НСТ-тесте, экспрессию HMGB1 – методом ELISA. 42-часовая гипоксия обусловливала альтернативную поляризацию ПМ с преобладанием аргиназной активности. NSC631570 вызывал реполяризацию метаболизма аргинина в гипоксических ПМ и активировал их провоспалительные функции: усиливал кислород-зависимый метаболизм и выделение аларминов. NSC631570 способен восстанавливать провоспалительные функции макрофагов, альтернативно поляризованных гипоксией. Гіпоксія є важливим фактором мікрооточення макрофагів. Багато важливих фізіологічних і пато-логічних процесів, у тому числі ріст солідних пухлин, характеризуються низьким тиском кисню і присутністю макрофагів. Пухлино-асоційована гіпоксія є однією з причин альтернативної поляризації макрофагів у пухлинній тканині, перетворю-ючи їх на клітини-союзники пухлинного процесу. Метою роботи було дослідження впливу NSC631570 – пухлино-селективного препарату зі здатністю вибірково накопичуватись у пухлинній тканині – на функції гіпоксичних макрофагів. Мишачі перитонеальні макрофаги (ПМ) піддавались гіпоксичній обробці (3 % O₂). Рівень нітритів вивчали в реакції Гріса. Аргіназну активність визначали колориметричним методом. Утворення внутрішньоклітинних реактивних форм кисню (РФК) і фагоцитоз аналізували за допомогою проточної цитофлюориметрії. Позаклітинну продукцію РФК визначали в НСТ-тесті, експресію HMGB1 – методом ELISA. 42-годинна гіпоксія спричиняла альтернативну поляри-зацію ПМ з переважанням аргіназної активності. NSC631570 викликав реполяризацію метаболізму аргініну у гіпоксичних ПМ і активував їх прозапальні функції: посилював киснезалежний метаболізм і виділення алармінів. NSC631570 здатний відновлювати прозапальні функції макрофагів, альтернативно поляризованих гіпоксією.